Uncertainty and hope - Tedesco, Juan Carlos (Avances en Supervisión Educativa, 2013)
A humanist paradigm of education and the future The decisions that citizens should take in the future are of an unprecedented scale: to include all or not, to manipulate or not our genetic capital, to care for or depredate nature, etc. The levels of reflexivity required to address these issues are profound and depend not only on vigorous cognitive development but also on ethical and moral development. How can intentional and systematic educational actions affect these levels of reflexivity? Which institutional forms will be the most appropriate? Who will be the educators of these training processes?